2008
DOI: 10.4049/jimmunol.180.11.7764
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Mediated by TLR5 as a Novel Antiinflammatory Target for Cystic Fibrosis Lung Disease

Abstract: Novel therapies to target lung inflammation are predicted to improve the lives of people with cystic fibrosis (CF) but specific antiinflammatory targets have not been identified. The goal of this study was to establish whether TLR5 signaling is the key molecular pathway mediating lung inflammation in CF, and to determine whether strategies to inhibit TLR5 can reduce the damaging inflammatory response. The innate immune responses were analyzed in both airway epithelial cells and primary PBMCs from CF patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 53 publications
9
82
1
3
Order By: Relevance
“…Importantly, flagellin-deficient P. aeruginosa bacteria were significantly impaired in inducing MDSCs, supporting the idea that the effect of P. aeruginosa in vivo and in vitro is mainly mediated through flagellin. The significance of the flagellin-TLR5 axis in P. aeruginosa-host interactions has been previously demonstrated in numerous studies, including experimental infection models using epithelial cells (1,2,5,17,19,20), macrophages (21), neutrophils (18), or in vivo infection strategies (3,22,23). Our study thereby confirms and extends the concept that flagellin acts as a key player in shaping the innate but also the adaptive immune response to P. aeruginosa in CF lung disease and beyond.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Importantly, flagellin-deficient P. aeruginosa bacteria were significantly impaired in inducing MDSCs, supporting the idea that the effect of P. aeruginosa in vivo and in vitro is mainly mediated through flagellin. The significance of the flagellin-TLR5 axis in P. aeruginosa-host interactions has been previously demonstrated in numerous studies, including experimental infection models using epithelial cells (1,2,5,17,19,20), macrophages (21), neutrophils (18), or in vivo infection strategies (3,22,23). Our study thereby confirms and extends the concept that flagellin acts as a key player in shaping the innate but also the adaptive immune response to P. aeruginosa in CF lung disease and beyond.…”
Section: Discussionsupporting
confidence: 77%
“…Because our CF patient cohort was characterized by a clear predominance of nonmucoid P. aeruginosa isolates and MDSCs tended to be higher in CF patients featuring nonmucoid than mucoid P. aeruginosa isolates, we speculate that P. aeruginosa-derived flagellin plays an essential role in MDSC induction, at least in pediatric CF cohorts. However, future studies in adult CF patients with a higher proportion of mucoid P. aeruginosa phenotypes, using methods such as the swimming motility assays (5), are required to assess whether motile P. aeruginosa and functional flagella are required to induce MDSCs in CF in vivo. Moreover, representative longitudinal studies should address the question whether MDSCs can be predictive for the course of CF lung disease, such as disease exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 TLR5 signaling is a key molecular pathway that mediates lung inflammation during cystic fibrosis. 21 The flagellin-TLR5 axis might also trigger cardiac innate immune responses and result in cardiovascular dysfunction. 22 Consistent with previous reports, 23,24 we previously demonstrated that either intranasally or intraperitoneally administered flagellin could induce a significant increase in the serum aminotransferase levels in mice, 25 suggesting that flagellin might be a potent inducer of liver damage.…”
Section: Introductionmentioning
confidence: 99%